Hubungan Dukungan Keluarga Terhadap Motivasi Menyelesaikan Skripsi pada Mahasiswa Tingkat Akhir di Fakultas Kedokteran Universitas Tanjungpura - Rusianti, Mitha Iska; Fahdi, Faisal Kholid; Righo, Argitya (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT The number of events that occur to students today is found that students say that their families often support them in doing their thesis (67.4%) however, sometimes students feel less motivated in doing their thesis (59.4%) with various causes including lazy habits, lack of support from the closest people, a classmate has finished his thesis so that he feels alone as well as internal and external factors. To determine the relationship between family support and motivation in completing thesis in final year students at the Faculty of Medicine, Tanjungpura University. This type of research is a quantitative research with a correlation design through a cross sectional approach. Population in this study were final year students who took thesis courses at the Faculty of Medicine, Tanjungpura University in 2022. The sampling technique in this study used Snowball Sampling with a sample of 114 people. Data analysis using pearson product moment. The results showed that most of the students received good family support as many as 86 people (75.4%) and all students had strong motivation as many as 114 people (100%). There is a relationship between family support and motivation to complete the thesis with a p value of 0.000 (<0.05) and a correlation value of 0.451 which indicates that the level of significance is moderate. There is a relationship between family support and motivation to complete a thesis at the Faculty of Medicine, Tanjungpura University. Keywords: Family Support, Motivation, Students.  ABSTRAK Angka kejadian yang terjadi pada mahasiwa saat ini ditemukan bahwa mahasiswa mengatakan keluarga sering mendukung dalam mengerjakan skripsi (67,4%) akan tetapi, kadang-kadang mahasiwa merasa kurang termotivasi dalam mengerjakan skripsi (59,4%) dengan berbagai penyebab diantaranya kebiasaan bermalas-malasan, kurangnya dukungan dari orang-orang terdekat, teman satu angkatan telah selesai skripsi sehingga merasa sendiri serta faktor internal dan eksternal. Mengetahui hubungan dukungan keluarga terhadap motivasi dalam menyelesaikan skripsi pada mahasiswa tingkat akhir di Fakultas Kedokteran Universitas Tanjungpura. Jenis penelitian adalah penelitian kuantitatif dengan desain korelasi melalui pendekatan cross sectional. Populasi dalam penelitian ini adalah mahasiswa tingkat akhir yang mengambil mata kuliah skripsi di Fakultas Kedokteran Universitas Tanjungpura tahun 2022. Teknik pengambilan sampel dalam penelitian ini menggunakan Snowball Sampling dengan sampel sebanyak 114 orang. Analisa data menggunakan pearson product moment. Hasil penelitian menunjukkan sebagian besar mahasiswa mendapatkan dukungan keluarga yang baik sebanyak 86 orang (75,4%) dan mahasiwa seluruhnya memiliki motivasi kuat sebanyak 114 orang (100%) dengan nilai p value 0,000 (<0,05) dan nilai r hitung 0,451 yang menunjukkan bahwa tingkat signifikansi sedang. Terdapat hubungan dukungan keluarga terhadap motivasi menyelesaikan skripsi di Fakultas Kedokteran Universitas Tanjungpura. Kata Kunci: Dukungan Keluarga, Motivasi, Mahasiswa.